(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
هدف هذا البحث إلى تقدير تراكيز العناصر الثقيلة (الزنك و النحاس والرصاص والكادميوم) في منطقتين من المياه الشاطئية لمدينة اللاذقية (رأس الشمرة و رأس ابن هاني)، وعند نوعين من الطحالب ( Sargassum closeup and Cystoseira amentacea) . أظهرت النتائج تبايناً واضحاً في تراكيز العناصر الثقيلة بين مياه المنطقتين المدروستين، حيث كانت تراكيز كافة العناصر المدروسة أكثر ارتفاعاً في منطقة رأس ابن هاني مقارنة بمنطقة رأس الشمرة، ويعود ذلك لتعرض منطقة رأس ابن هاني لنشاطات بشرية متنوعة ولوجود وعمل مراكب الصيد بكثافة أكبر مما هو عليه الحال برأس الشمرة. تباين نوعي الطحالب باحتوائهما على العناصر الثقيلة، حيث وجد ارتفاعاً بتراكيز العناصر الثقيلة عند النوع S. closeup مقارنة بالنوع C.amentacea . عند مقارنة تراكيز العناصر الثقيلة في المياه مع مثيله عند الطحالب تبين وجود تشابهاً بترتيب محتواهما من العناصر، حيث احتل الزنك أعلى نسبة في حين وجد الكادميوم بأقل نسبة، وكان ترتيب تراكيز العناصر الثقيلة هو: الزنك > الرصاص > النحاس > الكادميوم. Therefore, this study aimed to estimate the concentrations of heavy metals (Zn, Cu, Pb and Cd) in the water of two areas (Ras Alshamra and Ras Ibn Hani) on the shore of Lattakia City and in two algae species (Sargassum closeup and Cystoseira amentacea). The results showed a significant difference in the concentrations of heavy metals in the water of the two areas, where Ras Ibn Hani had higher concentrations than Ras Alshamra. This differences in concentrations are due to the presence of various human activities and to a higher number of fishing boats in Ras Ibn Hani comparing to Ras Alshamra. The analysis of algae species showed a higher level of heavy metals in S. closeup than the level in C. amentacea. The comparison of heavy metal concentrations between water and algae showed similar patterns. Zn was present in the highest concentration while Cd was in the lowest one. The concentration of heavy metals showed the following order: Zn> Pb> Cu> Cd.